2008
DOI: 10.1007/s11262-008-0240-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the genes coding for glycoprotein and L protein of lymphocytic choriomeningitis virus strain MX

Abstract: Lymphocytic choriomeningitis virus (LCMV) is the prototype Arenavirus with ambisense coding strategy. We have previously described a new MX strain LCMV and determined the primary structure of the genes coding for the nucleoprotein and RING finger Z protein. In this report, we describe amplification and sequencing of the entire coding sequences of additional MX genes, the glycoprotein precursor (GPC) and L protein. The obtained MX GPC cDNA sequence was 1,615 nucleotides long and contained an ORF, which encodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Analysis of the MX LCMV coding regions has revealed sequence differences supporting the view that MX is a separate LCMV strain (9,25,32). MX LCMV does not cause any cellular damage, and its host range is restricted to only few cell lines.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Analysis of the MX LCMV coding regions has revealed sequence differences supporting the view that MX is a separate LCMV strain (9,25,32). MX LCMV does not cause any cellular damage, and its host range is restricted to only few cell lines.…”
mentioning
confidence: 74%
“…It is transmissible by direct cell-to-cell contact or cell extract but not by filtered medium of infected cells (25). Furthermore, cells infected with MX LCMV accumulate high cytoplasmic levels of NP and ZP and contain deleted RNAs (9,25,32).…”
Section: Lymphocytic Choriomeningitis Virus (Lcmv) Ismentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis of the coding regions confirmed that MX represents a distinct strain of LCMV (14,31,37). The biological features of LCMV MX exhibited several similarities with those of other persistent LCMV strains.…”
mentioning
confidence: 76%
“…Recently we showed that MX NP binds and stabilizes keratin 1, a part of an intermediate filament network, and thereby facilitates LCMV transmission via cell-cell contacts (22). LCMV MX-infected cells accumulate high cytoplasmic levels of NP and Z and full-length as well as deleted viral RNAs (14,31,37). In comparison with other LCMV strains, MX has a more restricted host range (31).…”
mentioning
confidence: 99%